Compulsory collisions and corporate interests in school rugby: challenging distortions in the framing of childhood injury. Issue 1 (14th November 2022) - Piggin, Joe; Batten, John; Parry, Keith; Anderson, Eric; White, Adam J
Abstract : This article examines how 'framing' is used to resist a proposal to remove rugby tackling from UK schools. It focuses on rugby tackling for UK school children, which is often a compulsory part of many schools' curricula. Specifically, we explore the importance of framing in how the problem is described in various academic publications, how ideas about risk are articulated and how advocates themselves are represented. We show how the corporate interests of rugby governing bodies can become entangled with distortions about injury prevention. These distortions (or framing practices) include omitting arguments, conflating arguments, changing the argument, misrepresenting advocacy positions and skewing advocate identities. Next, the article demonstrates how a combination of recent advocacy, political interventions, research and cultural shifts appears to be changing perceptions about the risks associated with rugby tackling for children in school settings. In conclusion, we argue that while framing can be a useful strategy for policy advocates, there is value in paying attention to how framing is used by different stakeholder groups.